Implementanation of IT in local public sector - Đorđević, Snežana (Serbian political thought, 2023)
State and local governments in e-tools have important instruments of quality management and the creation and implementation of sectoral policies. Smart city projects provide excellent services to citizens, increase the transparency and accountability of authorities, as well as citizens' satisfaction with services.                Participative e- decision-making is useful because citizens are indispensable for expressing their needs, assessing the quality of services, and setting requests and initiatives (co-production). On the other hand, it is also important to include public servants who ensure that decisions are optimally shaped and that services are tailored according to the needs of specific people (personalization of services) and the community.      Serbia has a systemic problem of centralization, a top-down approach to management, weak participation of citizens and weak involvement of experts in the work of e-government. Good practice indicates that e-government cannot function without the active involvement of citizens, so our system needs to be changed and improved. These changes would also modernize management, decision making and policy making (evidence based decision and policy making). The consequence would be the creation of services according to the needs of citizens, which increases citizens' satisfaction with the quality of services. In addition, these processes strengthen the socialization of citizens, strengthen democratic capacities of communities, and raise the motivation of employees to contribute to the quality of work (strengthening of professionalization, motivation and dignity of public servants).
Keywords: Keywords: ICT aplications, e-government, open data basis, citizens’participation adn co-production, public servants’discretion and motivation